CARACTERIZAÇÃO DA PRODUÇÃO CIENTÍFICA NA ÁREA DE APROVEITAMENTO DE ÁGUA PLUVIAL - Rocha, Sarah Rocha; Campos, Marcus (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The use of rainwater has been highlighted in recent years as a way to promote water conservation in buildings. This relevance is reflected in important Brazilian academic publications. Thus, a survey of the articles published in the ENTAC and the Ambiente Construído Journal of the year 2004 up to the present was carried out, following a methodology proposed in Ilha et al. (2006). Through this analysis, it was verified that the year 2004 was the year with the largest number of publications, the Federal University of Santa Catarina, the most published institution on the subject, and that the publications on this subject usually have an approach to technical, economic and / or environmental feasibility. It was also verified that the most of researches have taken place in residential buildings and educational institutions. Based on this survey, it is possible to determine the areas not yet explored by these researches already carried out, increasing the limit of knowledge in this area.